Artistic Reflections of Cultural Continuity: Gedik Ahmet Pasha Mosque Hand-Drawn Decorations - İrteş, Muammer Semih; Baysal, Ali Fuat; Önkol Ertunç, Çiğdem (Journal of History Culture and Art Research, 2022)
Located in the center of the Afyon Gedik Ahmed Pasha Kulliye, the existing painted decorations of the mosque have remarkable features in terms of our decoration history. The painted decoration existing in some areas in the sanctuary of the mosque, which was built in the last quarter of the 15th century, are important examples that reflect the ornamental style of the period to the present and should be preserved in order to transfer it to the future. XVth century is an enthusiastic period in terms of Ottoman painted decoration art. In spite of the pessimism of the Interregnum Period and the Cem Sultan cases, in this process where brand new fantasies are revealed, the interiors of the buildings are completely decorated with inscriptions and embroidery. The patterns that we see in the architectural structures of Bursa and especially Edirne reveal the fact that they are in interaction with the decorations in the structures that have survived to the present day. These examples, which are the work of a tradition that has been layered for centuries; It has come to life with the skilful composition of the motifs that emerged as a result of the textures of the rich civilization of the Anatolian geography and the cultural values filtered from the Central Asian steppes. In addition to the intense use of rûmi, hatai and cross motifs in the designs, they have been handled in detail and the motifs were elaborately detailed.